2023
DOI: 10.3390/jcm12216849
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Anti-Synthetase Syndrome and Variables Associated with Interstitial Lung Disease and Mortality: A Retrospective Cohort Study

Tulaton Sodsri,
Tananchai Petnak,
Pintip Ngamjanyaporn

Abstract: Anti-synthetase syndrome (ASS) is a rare autoimmune disease. Since the knowledge of ASS remains limited, we conducted the retrospective study aiming to describe clinical characteristics and identify variables associated with interstitial lung disease (ILD) and mortality among patients with ASS. Patients diagnosed with ASS from January 2013 to October 2022 were included. Patient demographics, clinical manifestations, myositis auto-antibody profiles, HRCT findings, and laboratory tests were collected. Variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Positive results for anti–PL-12, anti–Jo-1, and anti–Ro-52 antibodies were reported in this case. Studies have shown that anti–Ro-52 antibodies in ASS patients are associated with RPILD [ 19 ], whereas anti–PL-12 antibodies are strongly associated with ILD development [ 20 ]. In a previous study, arthritis was the most common initial symptom in the anti–Jo-1 antibody-positive group [ 21 ], and in alignment with literature, our patient presented with multiple joint effusions.…”
Section: Discussionmentioning
confidence: 99%
“…Positive results for anti–PL-12, anti–Jo-1, and anti–Ro-52 antibodies were reported in this case. Studies have shown that anti–Ro-52 antibodies in ASS patients are associated with RPILD [ 19 ], whereas anti–PL-12 antibodies are strongly associated with ILD development [ 20 ]. In a previous study, arthritis was the most common initial symptom in the anti–Jo-1 antibody-positive group [ 21 ], and in alignment with literature, our patient presented with multiple joint effusions.…”
Section: Discussionmentioning
confidence: 99%
“…There are several important points regarding the association between mechanic’s hands and ASS that should be considered: the combination of mechanic’s hands, myopathy, and ILD is not exclusive to ASS; mechanic’s hands can be present in cases without detectable MSAs; the presence of mechanic´s hands, even without satisfying the criteria for ASS, is a risk factor for ILD, a potentially severe and recalcitrant condition if not detected early. [9,25–28,34–36]…”
Section: Discussionmentioning
confidence: 99%
“…Based on a targeted literature review using PubMed, previous studies utilized EIA or LIA alone for detecting anti-Ro52 antibodies and reported the prevalence of anti-Ro52 antibodies as 21.4-65.9% in patients with anti-synthetase antibodies [13][14][15][16][17][18][36][37][38][39][40][41] (Supplementary Table S1) and 31.5-74.7% in those with anti-MDA5 antibodies [13,[19][20][21][22][23][24] (Supplementary Table S2), respectively, which are compatible with the prevalence in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…For the patients with anti-MDA5 antibodies, 33 (97.1%) were either isolated anti-Ro52 positive or anti-Ro52 negative, and only one patient (2.9%) presented with anti-SSA-Ro52 positivity; therefore, we compared clinical characteristics between patients with and without isolated anti-Ro52 positivity (Table 2). Patients with isolated anti-Ro52 positivity were older than those without (65 [61-68] years old vs. 48 [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] years old, median [IQR]; p = 0.025). Of note, RP-ILD was more prevalent (75.0% vs. 30.8%, p = 0.042), the partial pressure of oxygen (PaO 2 )/fraction of inspired oxygen (FiO 2 ) ratio was lower (320.0 [270.2-373.4] vs. 416.7 [346.2-437.6], median [IQR]; p = 0.029), and the alveolar-arterial oxygen gradient (A-aDO 2 ) was higher (41.9 [30.4-54.2] vs. 19.2 [10.1-33.6], p = 0.019) in patients with isolated anti-Ro52 positivity than in those without.…”
Section: Clinical Characteristics and Outcomes Stratified By Isolated...mentioning
confidence: 99%
See 1 more Smart Citation